Comparison Between Fastica and Infomax for the Blind Separation of Audio Signals - Soto-Gomez, J; San Juan-Urrutia, E; Canete-Arratia, L; Adasme-Soto, P; Seguel-Gonzalez, F (Institute of Electrical and Electronics Engineers Inc., 2018)
This research presents a comparison between two blind separation techniques from sources, which are Fast independent component analysis (FastIca) and Maximization of Ica information (InfoMax). To do this, two audio signals are used, which will be input to the two separation techniques of blind sources and finally the yield will be measured using the mean square error method. © 2018 IEEE.